(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The present study investigates the comparative status of physico-chemical water quality parameters and fish diversity in two important freshwater reservoirs of Nashik district, Maharashtra, namely Ozarkhed Dam and Gangapur Dam. Freshwater ecosystems play a vital role in maintaining ecological balance, supporting aquatic biodiversity, and providing water resources for domestic, agricultural, and fishery purposes. The study was conducted to assess the seasonal variation in water quality and its influence on ichthyofaunal diversity in these reservoirs. Water samples were collected from both dams during three major seasons, namely Monsoon, Post-Monsoon, and Pre-Monsoon, and analyzed for selected physico-chemical parameters such as temperature, pH, dissolved oxygen (DO), biological oxygen demand (BOD), chemical oxygen demand (COD), turbidity, electrical conductivity (EC), total dissolved solids (TDS), total suspended solids (TSS), alkalinity, hardness, chlorides, nitrates, phosphates, sulphates, and ammonia. Simultaneously, fish diversity was assessed through field observations, local fish catch records, fishermen interactions, and taxonomic identification of fish species.